Das Sanatorium der Verwandlung. Zur „immerwährenden“ Kreativität der polnischen Rezeption von Thomas Manns Zauberberg - Dziergwa, Roman (Studia Germanica Posnaniensia, 2017)
The reception of Thomas Mann in Poland confirms its special nature, involving a very high degree of transforming processing and extraordinary creativity. It is true that the author of The Magic Mountain, and only he is and was considered in Poland as the German intellectual of the twentieth century par excellence. The more that in the case of this exceptional writer prominent Polish artists and creators of the culture didn’t succumb to a superficial and short-lived fascination, but rather they transformed the threads of his works and artistic biography in a highly productive process. Often there was no exaggeration to say about the "reinterpretation" or even a sort of "over-interpretation" of several biographical and literary motifs. The reception of Thomas Mann was not and is not merely occasional reception at most of an academic character. The rank and importance of eminent Polish writers, literary critics, translators and literary critics presented in the article show in best way the creativity of Polish references and positions taking to Thomas Mann and his work. No other of his novel can compete because of his inspiring role to a permanent creative activity reception area with regard to Magic Mountain. The newest and best prove for it is dating back to 2015 as two adaptation attempts of the novel in the form of opera and theatrical performance were in Poland discussed and extensively commented in the press and on the Internet and finally awarded with major prizes.